2022
DOI: 10.1021/acs.energyfuels.1c03877
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate-Based Gas Storage Application Using Simulated Seawater in the Presence of a Co-Promoter: Morphology Investigation

Abstract: The hydrate morphology pattern plays a critical role in the reactor design for hydratebased gas storage/separation technology. This work investigated the morphology of mixed methane− THF hydrate formation using salt water (3.5 wt % NaCl) instead of pure water at 288.2 K and 8 MPa. The result indicated that the nucleation occurred at the gas/liquid interface and then the hydrates grew along the wall of the crystallizer column. After a specific time interval, the hydrates gradually grew downward until they compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…Also, because of their large heat capacity, clathrate hydrate crystals may be used as a cold storage media at temperatures higher than that when ice is used . In addition, gas hydrates can selectively remove gases from gas mixtures, , as well as water from aqueous solutions such as with desalination. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, because of their large heat capacity, clathrate hydrate crystals may be used as a cold storage media at temperatures higher than that when ice is used . In addition, gas hydrates can selectively remove gases from gas mixtures, , as well as water from aqueous solutions such as with desalination. , …”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis to explain this memory effect is the “residual structure hypothesis”, which argues that sections of the hydrate crystal structure remain in water, thus leaving behind a “memory” of the crystal structure ,,, (see 2­(a) in Table ). In this explanation’s favor, it is known that a hydrogen bond network exists even with pure water, especially at the low temperatures involved in hydrate formation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a huge experimental effort has been directed to enhance methane hydrate kinetics from natural or simulated seawater (2.7-3.5 wt% NaCl) in non-stirred reactors 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nesterov and Reshetnikov examined pure methane hydrate formation from saline water (3 wt %) in the presence of 0.1 wt % SDS at 275 K. They found that SDS micelles did not form even if the pressure was increased from 8 to 16 MPa . Moreover, Inkong et al tested copromoters of SDS and amino acids for binary CH 4 –THF sII hydrates from a saline solution of 3.5 wt % NaCl at 8 MPa and 288 K. Despite the reduced induction time and increased hydrate formation rate in the presence of SDS, the process resulted in 50% reduction of methane uptake and hydrate yield compared to stand-alone amino acids. , Thus, the effect of SDS addition to saline water is the same in both sI and sII hydrate studies. In addition to the above adverse effects of SDS as a kinetic hydrate promoter (KHP), it has been found that it is not practical for any practical scale-up application due to severe foam formation even at low concentrations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation